2017
DOI: 10.1111/ddi.12557
|View full text |Cite
|
Sign up to set email alerts
|

Recreational freshwater fishing drives non‐native aquatic species richness patterns at a continental scale

Abstract: AimMapping the geographic distribution of non-native aquatic species is a critically important precursor to understanding the anthropogenic and environmental factors that drive freshwater biological invasions. Such efforts are often limited to local scales and/or to single species, due to the challenges of data acquisition at larger scales. Here, we map the distribution of non-native freshwater species richness across the continental United States and investigate the role of human activity in driving macro-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 67 publications
(103 reference statements)
1
28
0
Order By: Relevance
“…We recognize that NAS richness patterns are potentially skewed by the search effort associated with specific areas (Hoffman et al, 2011). While we do not have independent effort estimates, a recent continental-scale analysis of NAS richness patterns that included the Great Lakes found that spatial "hotspots" in NAS richness were the same pre-and post-data rarefaction, suggesting an effort effect is not sufficiently large at this Great Lakes scale to alter interpretation of richness patterns (Davis & Darling, 2017).…”
Section: Nas Richnessmentioning
confidence: 85%
“…We recognize that NAS richness patterns are potentially skewed by the search effort associated with specific areas (Hoffman et al, 2011). While we do not have independent effort estimates, a recent continental-scale analysis of NAS richness patterns that included the Great Lakes found that spatial "hotspots" in NAS richness were the same pre-and post-data rarefaction, suggesting an effort effect is not sufficiently large at this Great Lakes scale to alter interpretation of richness patterns (Davis & Darling, 2017).…”
Section: Nas Richnessmentioning
confidence: 85%
“…The ornamental fish trade is also a significant vector for invasive fishes (for example, Costa‐Pierce, ; Gozlan, Britton, Cowx, & Copp, ; Raghavan, Prasad, Anvar‐Ali, & Pereira, ). So too is fish stocking, both legal and illegal, in support of recreational angling (Davis & Darling, ), as well as accidental releases, such as bait releases, aquaculture escapes, or ballast water transport (Gupta & Everard, ; Lintermans, ). Notwithstanding the life‐history traits of individual species favouring the establishment of new populations, propagule pressure (i.e.…”
Section: Causes and Conservation Impacts Of Alien Freshwater Fish Intmentioning
confidence: 99%
“…A few studies have been undertaken to investigate the role of angling in the secondary dispersal of INNS between water bodies (Gates et al 2009;Anderson et al 2014), and others have reported the potential for INNS introduction and spread from the use of live bait by anglers (Keller et al 2007;Kilian et al 2012;Drake and Mandrak 2014;Cerri et al 2017). In North America, higher numbers of non-native species have also been found to coincide with areas of greater recreational fishing demand (Davis and Darling 2017). However, there have been limited, if any, studies undertaken to investigate the potential for long-distance jump dispersal of INNS between continents/countries on damp angling equipment.…”
Section: Introductionmentioning
confidence: 99%